2011
DOI: 10.1074/jbc.m111.233585
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Inorganic Triphosphatase from Nitrosomonas europaea

Abstract: The CYTH superfamily of proteins is named after its two founding members, the CyaB adenylyl cyclase from Aeromonas hydrophila and the human 25-kDa thiamine triphosphatase. Because these proteins often form a closed ␤-barrel, they are also referred to as triphosphate tunnel metalloenzymes (TTM). Functionally, they are characterized by their ability to bind triphosphorylated substrates and divalent metal ions. These proteins exist in most organisms and catalyze different reactions depending on their origin. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 56 publications
1
41
2
Order By: Relevance
“…Both AtTTM1 and 2 displayed low activity on ATP, ADP, or PPP i substrates, while high affinity was observed for PP i with a K m of 17 mM, which is comparable to the K m of AtTTM3 or NeuTTM for PPP i (43 mM and 21 mM, respectively; Moeder et al, 2013;Delvaux et al, 2011). We tested several biologically relevant diphosphates such as thiamine diphosphate (Jordan, 2007), ADP ribose (Adams-Phillips et al, 2010) and NADH (Ishikawa et al, 2010), all of which were not hydrolyzed by AtTTM1 and AtTTM2 (Ung and Yoshioka, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Both AtTTM1 and 2 displayed low activity on ATP, ADP, or PPP i substrates, while high affinity was observed for PP i with a K m of 17 mM, which is comparable to the K m of AtTTM3 or NeuTTM for PPP i (43 mM and 21 mM, respectively; Moeder et al, 2013;Delvaux et al, 2011). We tested several biologically relevant diphosphates such as thiamine diphosphate (Jordan, 2007), ADP ribose (Adams-Phillips et al, 2010) and NADH (Ishikawa et al, 2010), all of which were not hydrolyzed by AtTTM1 and AtTTM2 (Ung and Yoshioka, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
“…Known functions of TTMs include fungal and protozoan RNA triphosphatases (Cet1; Lima et al, 1999;Gong et al, 2006), bacterial adenylate cyclases (CyaB from Aeromonas hydrophila and YpAC-IV from Yersinia pestis; Sismeiro et al, 1998;Gallagher et al, 2006), and mammalian thiamine triphosphatases (Lakaye et al, 2004;Song et al, 2008). More recently, tripolyphosphatase activity was discovered for CthTTM from Clostridium thermocellum and NeuTTM from Nitrosomonas europaea, highlighting the functional diversity of this superfamily (Keppetipola et al, 2007;Delvaux et al, 2011). In some instances, TTM proteins can also possess additional domains, adding further complexity to their range of functions.…”
mentioning
confidence: 99%
“…So far, the exact biological function of TTM proteins in plants is not clear. We previously analyzed AtTTM3 and found that it does not display adenylate cyclase activity, despite its annotation, but it does act on PPPi and with lower affinity, nucleotide triphosphates, releasing inorganic phosphate, similar to the TTM proteins from Clostridium thermocellum (CthTTM) and Nitrosomonas europaea (NeuTTM; Keppetipola et al, 2007;Delvaux et al, 2011;Bettendorff and Wins, 2013;Moeder et al, 2013). Additionally, a transfer DNA (T-DNA) insertion knockout (KO) line of AtTTM3 displayed a delay in root growth as well as reduced length and number of lateral roots, suggesting a role for AtTTM3 in root development.…”
mentioning
confidence: 99%
“…Nevertheless, P 3 has never been reported in prokaryotes, in contrast to long-chain polyPs, although it is known as an intermediate in a number of biosynthetic pathways, e.g. as an intermediate of S-adenosylmethionine, and is generated in some enzymic processes (Bettendorff & Wins, 2013;Delvaux et al, 2011). In contrast to this, P 3 has been shown as a major polyP in acidocalcisomes of several parasitic protists (Moreno et al, 2000), the vacuole of yeast (Castro et al, 1995) and the halotolerant microalga Dunaliella (Pick & Weiss, 1991), and the acidocalcisome-like, mitochondrial and nuclear compartments of mammalian cells (Kumble & Kornberg, 1995;Abramov et al, 2007;Müller et al, 2009;Seidlmayer et al, 2012).…”
Section: D0mi26 Rhom4 Q3at H9 Chlc H B4 Sc Z3 Pe Lp B Q 0y Tp 7 9c H mentioning
confidence: 99%
“…A group of CYTH proteins named triphosphate tunnel metalloenzymes (TTMs) has been found recently in some bacteria (e.g. Clostridium thermocellum, Nitrosomonas europaea) (Keppetipola et al, 2007;Delvaux et al, 2011) and the plant Arabidopsis thaliana (Moeder et al, 2013), and was reported to be composed of highly specific inorganic tripolyphosphatases. However, the specific metabolic roles of TTM proteins and their contribution, together with the more widespread Ppx-GppA phosphatases, to the ubiquitous tripolyphosphatase activity have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%